A novel Bayesian seamless phase I/II design. - Haitao Pan (Public Library of Science (PLoS), 2013)
This paper proposes a novel bayesian phase I/II design featuring using a hybrid mTPI method in phase I for targeting the MTD level and a randomization allocation schema for adaptively assigning patients to desirable doses in phase II. The mechanism of simultaneously escalating dose in phase I and expanding promising doses to phase II is inherited from a design proposed in literature. Extensive simulation studies indicate that our proposed design can vastly save sample size and efficiently assign more patients to optimal dose when compared to two competing designs.